2018
DOI: 10.1186/s12864-018-4760-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health and germline transmission in transgenic cattle following transposon-mediated gene transfer

Abstract: BackgroundTransposon-mediated, non-viral gene delivery is a powerful tool for generating stable cell lines and transgenic animals. However, as multi-copy insertion is the preferred integration pattern, there is the potential for uncontrolled changes in endogenous gene expression and detrimental effects in cells or animals. Our group has previously reported on the generation of several transgenic cattle by using microinjection of the Sleeping Beauty (SB) and PiggyBac (PB) transposons and seeks to explore the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…As such, various characteristics are divided according to the type of transposon. Previous in vivo experiments in our laboratory have produced transgenic cattle using PB and SB and have shown germ line transmission for more than 6 years without health problems (23). The embryo results of this experiment showed that not only PB and SB, but also Tol2, are highly e cient and Tol2 can be used as an alternative to PB and SB.…”
Section: Discussionmentioning
confidence: 79%
“…As such, various characteristics are divided according to the type of transposon. Previous in vivo experiments in our laboratory have produced transgenic cattle using PB and SB and have shown germ line transmission for more than 6 years without health problems (23). The embryo results of this experiment showed that not only PB and SB, but also Tol2, are highly e cient and Tol2 can be used as an alternative to PB and SB.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, all selected serum biochemistry parameters were also within physiological ranges, thus, rabbits had no any severe diseases ( Table 2 ). Normal serum biochemistry and hematology parameters were also observed in CAG-EGFP transgenic cattle (Yum et al . 2018), EGFP transgenic piglets (Carter et al .…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, various characteristics are divided according to the type of transposon. Previous in vivo experiments in our laboratory have produced transgenic cattle using PB and SB, which have shown germline transmission for more than 6 years without health problems [ 25 ]. The embryo results of this experiment demonstrate that PB, SB, and Tol2 are highly efficient and that Tol2 can be used as an alternative to PB and SB.…”
Section: Discussionmentioning
confidence: 99%